Comutations in DDR Pathways Predict Atezolizumab Response in Non-Small Cell Lung Cancer Patients - Xiong, Anning; Nie, Wei; Zhou, Yan; Li, Changhui; Gu, Kai; Zhang, Ding; Chen, Shiqing; Wen, Fengcai; Zhong, Hua; Han, Baohui; Zhang, Xueyan (Frontiers in Immunology, 2021)
The presence of comutations (co-mut+) in DNA damage response and repair (DDR) pathways was associated with improved survival for immune checkpoint inhibitors (ICIs) therapy in non-small cell lung cancer (NSCLC). However, it remains unknown whether co-mut+ status could be a predictive biomarker for immunotherapy. We aimed to explore the predictive role of co-mut+ status in the efficacy of ICIs. A total of 853 NSCLC patients from OAK and POPLAR trials were included in the analyses for the relationship between co-mut status and clinical outcomes with atezolizumab treatment. In co-mut+ NSCLC patients, significantly prolonged progression-free survival (PFS) (P = 0.004) and overall survival (OS) (P < 0.001) were observed in atezolizumab over docetaxel. The interaction between co-mut status and treatment was significant for PFS (P for interaction = 0.010) and OS (P for interaction = 0.017). In patients with negative or low programmed death receptor-ligand 1 expression, co-mut+ status still predicted improved clinical outcomes from atezolizumab therapy. These findings suggested that co-mut status may be a promising predictor of ICIs therapy in NSCLC.